PENINGKATAN PENGETAHUAN SANITASI MASYARAKAT KAMPUNG TRIDI KOTA MALANG MELALUI SOSIALISASI SEPTIC TANK UNTUK PEMUKIMAN PADAT PENDUDUK - Anie Yulistyorini; M.Mirza Abdillah Pratama; M.Musthofa Al Ansyorie; Gilang Idfi; Roro Roro (Politeknik Negeri Sriwijaya, 2020)
Kampong Tridi has become one of referable tourism destinations in Malang city. Instead of being renowned among locals, the kampong still has several issues to struggle regarding environmental management, specifically communal wastewater treatment. Septic tank as blackwater treatment system is not installed in residence majority which is about 63% of total number. This circumstance makes them directly dispose waste into Brantas River. The purpose of this socialization is to make the community aware of the importance of treating wastewater before disposal including steps to keep living environment. T test result showed the effect of socialization to the community’s environmental awareness through pretest and posttest comparison (p = 0.0004). To recapitulate, we conclude that this socialization brings significant positive impact to local’s environmental preservation awareness.